Cellular-Membrane-Derived Vesicles for Cancer Immunotherapy - Xiaoyu An; Yun Zeng; Chao Liu; Gang Liu (MDPI AG, 2023)
The medical community is constantly searching for new and innovative ways to treat cancer, and cellular-membrane-derived artificial vesicles are emerging as a promising avenue for cancer immunotherapy. These vesicles, which are derived from mammal and bacteria cell membranes, offer a range of benefits, including compatibility with living organisms, minimal immune response, and prolonged circulation. By modifying their surface, manipulating their genes, combining them with other substances, stimulating them externally, and even enclosing drugs within them, cellular vesicles have the potential to be a powerful tool in fighting cancer. The ability to merge drugs with diverse compositions and functionalities in a localized area is particularly exciting, as it offers a way to combine different immunotherapy treatments for maximum impact. This review contains information on the various sources of these vesicles and discusses some recent developments in cancer immunotherapy using this promising technology. While there are still obstacles to overcome, the possibilities for cellular vesicles in cancer treatment are truly exciting.